Youth pathways: evaluating the influence of gender : involvement with the public mental health system, perceived mental health need, and traumatic experiences on juvenile justice system processing - Espinosa, Erin M. (Youth violence and juvenile justice, 2020)
This study examined the influence of gender, participation in public mental health services, perceived mental health need, and traumatic experiences on juvenile justice system processing. Data were collected on youth formally processed for delinquency or status offenses by a large statewide juvenile justice system and youth served by the state’s public mental health system during a 7-year period (n ¼ 271,427). The results indicated that accessing mental health services in the community or being viewed as having a mental health need by a juvenile probation officer increased the like- lihood of youth being removed from their home by the juvenile justice system, especially for girls. While girls generally had decreased odds of out-of-home placement compared to boys, their odds significantly increased when combined with involvement in public mental health services and/or receiving a violation of probation. Once placed out of the home, boys discharged much more quickly than girls, with the rate of discharge being related primarily to the severity of their offenses. When controlling for relevant variables using propensity score matching, girls who experienced trauma or involvement with the public mental health system had a significantly lower rate of discharge from out-of-home placement than similarly matched boys.